Helen Keller : a life - Herrmann, Dorothy (1998)
"Dorothy Herrmann's biography of Helen Keller takes us through Helen's long, eventful life, a life that would have crushed a woman less stoic and adaptable - and less protected. She was either venerated as a saint or damned as a fraud. And one of the most persistent controversies surrounding her had to do with her relationship to the fiercely devoted Annie, through whom she largely expressed herself. Dorothy Herrmann explores these questions: Was Annie Sullivan a "miracle worker" or a domineering, emotionally troubled woman who shrewdly realized that making a deaf-blind girl of average intelligence appear extraordinary was her ticket to fame and fortune? Was she merely an instrument through which Helen's "brilliance" could manifest itself? Or was Annie herself the genius, the exceptionally gifted and sensitive one?" "Herrmann describes the nature of Helen's strange, sensorily deprived world. (Was it a black and silent tomb?) And she shows how Helen was so cheerful about her disabilities, often appearing in public as the soul of radiance and altruism. (Was it Helen's real self that emerged at age seven, when she was transformed by language from a savage, animal-like creature into a human being? Or was it a false persona manufactured by the driven Annie Sullivan?)" "Dorothy Herrmann tells why, despite her romantic involvements, Helen was never permitted to marry. She shows us the woman who, to communicate with the outside world, relied totally on those who knew the manual finger language. For almost her entire life, these people, some of whom were jealous or dogmatic, were the key to Helen's world."--BOOK JACKET.
Includes bibliographical references (p. 375-378) and index.
Keywords: Keller, Helen, -- 1880-1968.; Deafblind women -- Biography